The use of haemoglobin and body mass index as predictors of mortality in HIV patients newly initiated on highly active antiretroviral therapy - Tesfay, Abraham Rezene (My University, 2013)
Background: More than 33 million people are estimated to be living with HIV worldwide. Sub-Saharan Africa bears a disproportionate share of the global HIV burden. An estimated 15 million people living with HIV in low and middle income countries were in need of (HAART) in December 2009. HAART services require advanced laboratory technologies to monitor disease progression and therapeutic response, which are scarce in developing countries. Several simple and widely available markers have been proposed for use in low income countries including total lymphocyte count (TLC), haemoglobin and body mass index. Methodology: This study is a secondary data analysis of prospectively collected cohort data from HIV positive adults. The study measured the effect of exposure variables of haemoglobin (Hb) and body mass index (BMI). All cause mortality was the outcome of interest. Crude estimates of mortality were made with Kaplan-Meier mortality curves. Cox proportional hazards models were used to estimate adjusted hazard ratios. Exposure status was considered at initiation period. Outcomes were measured from two weeks post initiation of treatment to a maximum of two years of follow-up period. A composite score was developed to estimate the overall risk of mortality. Results: A total of 11,884 patients who satisfied the inclusion criteria were included in the analysis. A total of 1,305 deaths were observed during the follow-up period, representing 10.2% of the cohort at baseline. Most of the deaths were observed during the first four months of follow-up period. Patients with moderated to severe anaemia experienced 2.6 (HR = 2.6, 95% CI 1.8 - 3.6) times greater hazard of mortality adjusted for possible confounders. Patients with very iv low BMI experienced twice (HR=2.0, 95% CI 1.6, -2.5) greater hazard of mortality adjusted for a list of predictors. Race, age at initiation, employment status, smoking, alcohol consumption, baseline TB and baseline WHO stage did not show significant effect in the multivariate cox regression model. A composite score was developed to estimate the overall risk of mortality in patients based on measurements of baseline BMI and haemoglobin. Cox regression model adjusted for CD4 cell count shows high risk patients experienced 4.7 (HR = 4.7, 95% CI 2.9 – 7.6) times greater hazard of mortality compared to patients in the low risk group. Patients in the medium risk group experienced 3.4 (HR = 2.6, 95% CI 2.6 – 4.4) times greater hazard of mortality as opposed to patients in the low risk group. Conclusion: Haemoglobin and body mass index provide excellent prognostic information independent of CD4 cell count in HIV positive patients newly initiated on HAART. They can be used to reliably predict mortality. Combining measurements of haemoglobin and BMI through composite scoring improves their predictive ability. They can have good clinical application in rural and remote facilities to screen patients for clinical and diagnostic services.
A Research Report Submitted to the School of Public Health, University of the Witwatersrand, Johannesburg, in Partial Fulfilment of the Requirements for the Degree of Master of Science in Medicine in the Field of Epidemiology and Biostatistics: March 25, 2013
Keywords: Antiretroviral Therapy, Highly Active; HIV Infections--mortality